Synthesis of Fe-Si-B-Mn-based nanocrystalline magnetic alloys with large coercivity by high energy ball milling - Reddi P.D.; Mukhopadhyay N.K.; Majumdar B.; Singh A.K.; Meena S.S.; Yusuf S.M.; Prasad N.K. (My University, 2025)
Alloys of Fe-Si-B with varying compositions of Mn were prepared using high energy planetary ball mill for maximum duration of 120 h. X-ray diffraction (XRD) analysis suggests that Si gets mostly dissolved into Fe after 80 h of milling for all compositions. The residual Si was found to form an intermetallic Fe3Si. The dissolution was further confirmed from the field emission scanning electron microscopy/energy dispersive X-ray analysis (FE-SEM/EDX). With increased milling time, the lattice parameter and lattice strain are found to increase. However, the crystallite size decreases from micrometer (75-95 μm) to nanometer (10-20 nm). Mössbauer spectra analysis suggests the presence of essentially ferromagnetic phases with small percentage of super paramagnetic phase in the system. The saturation magnetization (Ms), remanance (Mr) and coercivity (Hc) values for Fe-0Mn sample after 120 h of milling were 96·4 Am2/kg, 11·5 Am2/kg and 12·42 k Am -1, respectively. However, for Fe-10Mn-5Cu sample the Ms, Hc and Mr values were found to be 101·9 Am 2/kg, 10·98 kA/m and 12·4 Am2/kg, respectively. The higher value of magnetization could be attributed to the favourable coupling between Mn and Cu.